Comparison of the Effectiveness of CO2 and Diode Lasers for Gingival Melanin Depigmentation: A Randomized Clinical Trial: CO2 and Diode Lasers for Gingival Depigmentation - Moeintaghavi, Amir; Ahrari, Farzaneh; Fallahrastegar, Amir; Salehnia, Asma (Journal of Lasers in Medical Sciences, 2022)
Introduction: Gingival hyperpigmentation is an esthetic concern for some individuals. This study compared the effectiveness of CO2 and diode lasers for gingival depigmentation. Methods: This randomized, split-mouth, clinical trial consisted of 12 patients with the chief complaint of hyperpigmented gingival areas. The upper right and left anterior segments and the mandibular anterior segment were randomly allocated to one of the treatment groups. The segments in group 1 underwent gingival depigmentation with a diode laser (810 nm) at 6 W and pulsed mode, whereas group 2 was ablated with a diode laser at 3 W and continuous mode. The removal of gingival pigments in group 3 was contemplated with a CO2 laser (10600 nm, 3 W, continuous mode). The operation chair time, bleeding during the procedure and post-operative pain were recorded. The gingival color and esthetic appearance were measured before the operation and at 1 week and 6 months later. Results: There was no significant difference in the bleeding scores, pain level, and color alteration values between the groups (P>0.05). The operation chair time was significantly shorter when the diode laser was applied at pulsed mode (P<0.05). The segments treated with the diode laser (pulsed or continuous mode) showed a higher esthetic appearance at the 6-month follow-up compared to those ablated with the CO2 laser (P<0.05). Conclusions: Higher esthetic appearance is expected when using the diode laser for gingival depigmentation compared to the CO2 laser. The application of the diode laser at pulsed mode could be recommended for gingival depigmentation, as it produced pleasing esthetic outcomes at reduced chair time. DOI:10.34172/jlms.2022.8